2015
DOI: 10.1016/j.neubiorev.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

False positive rates in Voxel-based Morphometry studies of the human brain: Should we be worried?

Abstract: Voxel-based Morphometry (VBM) is a widely used automated technique for the analysis of neuroanatomical images. Despite its popularity within the neuroimaging community, there are outstanding concerns about its potential susceptibility to false positive findings. Here we review the main methodological factors that are known to influence the results of VBM studies comparing two groups of subjects. We then use two large, open-access data sets to empirically estimate false positive rates and how these depend on sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 40 publications
(78 reference statements)
4
57
1
Order By: Relevance
“…First, studies are needed to determine whether the novel pattern of alterations we observed can be replicated, and whether they change over the course of drug treatment, acute clinical stabilization and over the longer term course of the illness. Fifth, we note that the VBM procedure we used is susceptible to false positive results [Scarpazza et al, 2015], and future studies are needed to extend our findings using other surface-based morphological measures, such as cortical thickness or surface area to validate and clarify our findings. It has been recently documented that similarity-based patterns of cortical morphology may arise from systematic functional co-activation and/or mutually trophic reinforcement, genetic mediated brain maturation, as well as experience-related plasticity [Alexander-Bloch et al, 2013;Evans, 2013].…”
Section: Limitationsmentioning
confidence: 80%
“…First, studies are needed to determine whether the novel pattern of alterations we observed can be replicated, and whether they change over the course of drug treatment, acute clinical stabilization and over the longer term course of the illness. Fifth, we note that the VBM procedure we used is susceptible to false positive results [Scarpazza et al, 2015], and future studies are needed to extend our findings using other surface-based morphological measures, such as cortical thickness or surface area to validate and clarify our findings. It has been recently documented that similarity-based patterns of cortical morphology may arise from systematic functional co-activation and/or mutually trophic reinforcement, genetic mediated brain maturation, as well as experience-related plasticity [Alexander-Bloch et al, 2013;Evans, 2013].…”
Section: Limitationsmentioning
confidence: 80%
“…Our findings should be considered preliminary, given group sizes that were comparatively small for VBM studies. However, while single case VBM studies are extremely susceptible to high false positive rates and thus should be avoided, a recent study revealed no significant impact of sample size (n=8, 12, and 16) on detecting false positive group differences (Scarpazza et al, 2015). We also did not include a comparison group of non-deployed veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, automated imaging analysis output of identical digital MR data may differ depending on the operating system used to run the program (Gronenschild et al 2012). When comparing studies and findings it remains critical that attention be directed to matters related to sample size, degree of smoothing and image modulation to keep false positive rates low (Scarpazza et al 2015). So automated methods provide great opportunity to assess large datasets Note that through this method the major regions of interest and brain nuclei may be identified and quantified but still require operator input and vigilance with regards to quality assurance and, to date, unresolved issues remain that relate to generalizability of findings across different acquisition sites and MR platforms (Chalavi et al 2012;Diaz-deGrenu et al 2014;Durand-Dubief et al 2012;Liem et al 2015;Nakamura et al 2014).…”
Section: Overview Of Structural Neuroimaging Analysesmentioning
confidence: 99%